(untitled) (Research, Society and Development, 2020)
Given the potential for commercial exploitation of E. spectabile and aiming to curb predatory extractivism, the development of researches that guide its cultivation becomes relevant. This study aims to evaluate the effects of different substrates and seed positions at sowing on the germination and vigor of seeds from two geographical regions. The experiment design was completely randomized in a 2 x 4 x 2 factorial design (seeds from two geographic regions: i.e., Serra Talhada-PE and Graça-CE, both in Brazil; four substrates: blotting paper, sand, vermiculite and coconut fiber: and two sowing positions: over and in between the substrate). Sowing on blotting paper, sand, vermiculite and coconut fiber, in general, was favorable to germination and germination speed index for seeds from both geographic regions. Sowing in between coconut fiber was detrimental to germination and root development regardless of the seed geographical region. However, sowing in between and over coconut fiber and in between sand favored shoot growth. The best combinations for dry matter production were sowing over paper and sand. The substrates blotting paper, sand, coconut fiber and vermiculite are favorable to E. spectabile seed germination regardless of geographic regions, provided that the sowing is made over the substrates.